2014
DOI: 10.17509/jrak.v2i2.6589
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Partisipasi Anggaran Terhadap Senjangan Anggaran: Komitmen Organisasi Dan Ketidakpastian Lingkungan Sebagai Variabel Moderating

Abstract: This research purpose to examine the effect budgetary participation on budgetary slack and moderation organizational commitment and enviroment uncertainty at budget participation on budgetary slack. This research used descriptive verification method. The sampling technique is non probablity sampling with  propotional sampling technique. The samples is 142 people from the entire population. The unit of analysis is the head/ field/ sub division in SKPD Serang. data was collected with direct distribution by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
2
0
2
Order By: Relevance
“…Therefore, with this condition, organizational commitment does not affect the relationship between budget participation and budgetary slack. The results of this study are supported by research conducted by Fatmawati & Widyaningsih (2014) and Adikusuma & Mukhzarudfa (2017) which explained that organizational commitment is not able to moderate the relationship between budget participation and budgetary slack.…”
Section: Hypothesis Testsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, with this condition, organizational commitment does not affect the relationship between budget participation and budgetary slack. The results of this study are supported by research conducted by Fatmawati & Widyaningsih (2014) and Adikusuma & Mukhzarudfa (2017) which explained that organizational commitment is not able to moderate the relationship between budget participation and budgetary slack.…”
Section: Hypothesis Testsupporting
confidence: 79%
“…There are several studies on several factors that can moderate the relationship between budgetary participation and budgetary slack, but show inconsistent results such as the organizational commitment variable studied by Irfan et al, (2016), Perdana & Yasa (2017), Negara & Wirajaya ( 2018), Riliana (2018) which showed that organizational commitment could moderate the relationship between budget participation and budgetary slack. However, Fatmawati & Widyaningsih (2014) and Adikusuma & Mukhzarudfa (2017) explained otherwise. Furthermore, the locus of control variable studied by Pello (2014), Adikusuma &Mukhzarudfa (2017), andPranata &Putri (2017) showed that locus of control could moderate the relationship between budgetary participation and budgetary slack.…”
Section: Introduction 11 Research Backgroundmentioning
confidence: 98%
“…Their belief that a budget that can be realized properly in the public interest can be achieved, it makes a pride in their belief. This result is supported by the research of Rahmiati (2013), Kartika (2010), Fatmawati andWidyaningsih (2014), andKusuma (2017). However, it is inconsistent with the research of Mulyani (2012), Marfuah and Listiani (2014), Apriantini et al (2014) which states the commitment of organizations to moderate the effect of participation in budgeting on budget gaps.…”
Section: The Effect Of Participatory Budgeting On Budget Slack With O...supporting
confidence: 60%
“…Komitmen organisasi adalah ikatan keterkaitan individu dengan organisasi. Komitmen menunjukkan keyakinan dan dukungan yang kuat terhadap nilai dan sasaran (goal) yang ingin dicapai oleh organisasi, bagi individu berkomitmen tinggi, pencapaian tujuan organisasi merupakan hal penting yang harus dicapai serta berpandangan positif dan berbuat yang terbaik untuk kepentingan organisasi (Fibrianti, D. and Riharjo, 2013). Hal ini berarti bahwa individu yang memiliki komitmen tinggi akan lebih mengutamakan kepentingan organisasinya daripada kepentingan pribadi atau kelompoknya.…”
Section: Pengaruh Komitmen Organisasi Terhadap Kinerja Manajerial Asnunclassified